Psychological and pedagogical conditions for the prevention of suicidal behavior among adolescents - Bodikova, Ләззат (Рroblems of engineering and professional education, 2022)
The article analyzed and identified the main factors of suicidal behavior of children and adolescents during the study of the causes of suicidal behavior of children and adolescents. Prevention of suicidal activity among adolescents, conducting diagnostic, corrective, psychoprophylactic work, preservation of life is the main task of psychologists.